If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4f + 7 = -5f Reorder the terms: 7 + -4f = -5f Solving 7 + -4f = -5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '5f' to each side of the equation. 7 + -4f + 5f = -5f + 5f Combine like terms: -4f + 5f = 1f 7 + 1f = -5f + 5f Combine like terms: -5f + 5f = 0 7 + 1f = 0 Add '-7' to each side of the equation. 7 + -7 + 1f = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1f = 0 + -7 1f = 0 + -7 Combine like terms: 0 + -7 = -7 1f = -7 Divide each side by '1'. f = -7 Simplifying f = -7
| 3/4x+2=7 | | 15=2x+75 | | 10(9+2n)= | | X+26+6=3x+6 | | d=2/3c | | 3/5k=2 | | -4/7*9 | | a=6(a+4) | | 4x+3x-10=11 | | 2(5f+9)= | | 3w^2-6w=24 | | (4/(3b-2))-(7/(3b+2)) | | (-7/11)*(2/5) | | 4x+8-7x=-22 | | 5+5b=5(1+5b) | | m=9+10m | | M/6-1=6 | | 7n-7=5n+7 | | 235=45X | | 7m-4=8m+5-m | | -8=6x+10 | | -6-3n=-6n | | 4x-33+3x+22=180 | | 4x-33+3x+22=180 | | 12-(6v+7)=-6v-5 | | -8s-5=-9s+5 | | -3+(-7-10)+4(6-10)= | | 11x+7x= | | -6a^2b= | | 2+4a-8a=5a+4 | | 3/16c=-15/4 | | -8y+7=-8y-9 |